The Effect of Warm Blankets on Body Temperature in Hypothermic Post-Caesarean Patients - Umifa, Kaslinda Nur Umifa; Abdur Rahim; Merisdawati MR (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Hypothermia is one of the disorders that often occurs in post-operative patients, hypothermia is a condition when body temperature drops to below 36.5oC. One type of surgery that often experiences hypothermia is a cesarean section (CS) which is caused by the use of anesthetic drugs that can suppress the rate of oxidative metabolism, thereby reducing metabolic heat production. One method that can be given to overcome hypothermia is by providing a regular blanket, but with the development of technology, non-pharmacological methods that can be developed are by providing a blanket warmers. The purpose of this study aims to determine the effect of giving blanket warmers on increasing body temperature in post caesarean section (CS) patients. This study was a quasi-experimental design with one group pretest-posttest. The research subjects included hypothermic post caesarean section (CS) patients with SAB anesthesia at Hospital Dr. Mohamad Soewandhi Surabaya. Sample selection was carried out using the total sampling technique with a sample size of 33 respondents. The results demonstrate that a 30-minute application of a blanket warmer significantly increased body temperature in postoperative patients under spinal anesthesia (p = 0.000). This supports the effectiveness of external warming in managing hypothermia, a common complication of spinal anesthesia, and highlights its clinical relevance in improving postoperative thermal stability.